Dosage Parameters in Pediatric Outcome Studies Reported in 9 Peer-Reviewed Occupational Therapy Journals from 2008 to 2014: A Content Analysis. (2nd February 2016) - Gee, Bryan M.; Lloyd, Kimberly; Devine, Nancy; Tyrrell, Erin; Evans, Trisha; Hill, Rebekah; Dineen, Stacee; Magalogo, Kristin
Abstract : Occupational therapists determine the dosage when establishing the plan of care for their pediatric clients. A content analysis was conducted using 123 pediatric occupational therapy outcomes studies from 9 scholarly international occupational therapy journals. The parameters of dosage were calculated using descriptive statistics in order to obtain a representation of dosage available within the current collage of pediatric occupational therapy outcomes studies. The results revealed that most studies reported portions of dosage parameters within the published studies. The average findings for the subcomponents related to dosage were session length (minutes) M = 58.7, duration of plan of care (weeks) M = 12.1, session frequency (per week) M = 3.4, and total hours of therapy (hours) M = 18.1 . This first attempt at describing and calculating dosage related to pediatric occupational therapy practice indicates that evidence is lacking within the published literature to adequately guide OT dosage decisions. Further research related to dosage in pediatric occupational therapy practice is needed.